2009
DOI: 10.3390/ijms10083283
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Microcalorimetry to Investigate Non Specific Interactions in Biophysical Chemistry

Abstract: Isothermal titration microcalorimetry (ITC) is mostly used to investigate the thermodynamics of “specific” host-guest interactions in biology as well as in supramolecular chemistry. The aim of this review is to demonstrate that ITC can also provide useful information about non-specific interactions, like electrostatic or hydrophobic interactions. More attention will be given in the use of ITC to investigate polyelectrolyte-polyelectrolyte (in particular DNA-polycation), polyelectrolyte-protein as well as prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 158 publications
3
62
0
2
Order By: Relevance
“…All the de-binding data were fitted to the predicted kinetics of release for the limiting cases of pure diffusion control and surface resistance control. The results showed that the coefficient of internal diffusion and surface permeability both increased with increasing temperature, suggesting that the de-binding process involved an increase in entropy, as expected for non-specific interactions (Ball & Maechling, 2009). The data showed that pectin transfer from inside to outside of composites was dominated by the surface permeability, similar to the previous study of de-binding behaviour of arabinan/galactan (Lin et al, 2015).…”
Section: De-binding Process To Investigate Reversible Interactions Ofsupporting
confidence: 66%
“…All the de-binding data were fitted to the predicted kinetics of release for the limiting cases of pure diffusion control and surface resistance control. The results showed that the coefficient of internal diffusion and surface permeability both increased with increasing temperature, suggesting that the de-binding process involved an increase in entropy, as expected for non-specific interactions (Ball & Maechling, 2009). The data showed that pectin transfer from inside to outside of composites was dominated by the surface permeability, similar to the previous study of de-binding behaviour of arabinan/galactan (Lin et al, 2015).…”
Section: De-binding Process To Investigate Reversible Interactions Ofsupporting
confidence: 66%
“…Supportive of this assignment is how this event was demonstrated to be entropy driven (Fig. 7a) as are most polyelectrolyte interactions, which are driven by the release of bound counterions and water upon complexation [54,[56][57][58][59][60]. The binding constant we determined for unconjugated PEI (7.6 × 10 8 M −1 ) is larger than that reported by Utsuno et al (1 × 10 6 M −1 ), but that study investigated a much smaller 600 Da branched PEI and linear, salmon testes DNA [46].…”
Section: Polymermentioning
confidence: 54%
“…3 and 4). ITC is one of the most powerful approaches for elucidating the physical, mechanical, and energetic natures of binding systems including molecular association mechanisms, binding modes, and driving forces for complexation [2,3,39].…”
Section: Fd-fnr Interactions Under Thermodynamic Controlsmentioning
confidence: 99%